PROFIL MODUL EVOLUSI UNTUK MELATIH BERPIKIR KRITIS SISWA SMA KELAS XII - MINARTI, (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2014)
The purpose of this research is to describe theoretically appropriate and empirical validity of the students' response to the evolution module. Evolution module tested on a limited basis to high school students of class XI Kemala Bhayangkari 1 Surabaya as many as 20 children.The instrument that is being used is validation sheet. This research use 4-D models. Results showed that the developed evolution module of critical thinking is appropriate to be used. Keywords: evolution module, critical thinking and the evolution of matter.